1981
DOI: 10.1002/iroh.19810660603
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Losses due to Zooplankton Grazing in a Drinking Water Reservoir

Abstract: Phptoplankton losses due to zooplankton grazing in the Saidenbach drinking wnter reservoir were ralrulated on the basis of laboratory experiments and field studies. The dependence of grazing rate and filtering rate on phytoplankton concentration, temperature and other factors is described.The amount of wnter filtered daily by the zooplankton population is 100-200 ml/l. d. Thegrazing performance of the zooplankton thus sometimes exceeds the growth rate of the phytoplankton population and leads to its decimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…The ILC of 2.7 x lo3 yg l-' for a 1 mm field cladoceran (Fig. 3) agrees well with 2.8 x lo3 lug l-I, the ILC value for a 1.1 mm D. hydina (Horn, 1981; Table 5). The results of this comparison suggest that laboratory data may be directly applicable to the field where high food concentrations are involved, although data corresponding to more dilute concentrations should not be extrapolated without scrutiny.…”
Section: Comparison Of Ilc Valuessupporting
confidence: 71%
See 1 more Smart Citation
“…The ILC of 2.7 x lo3 yg l-' for a 1 mm field cladoceran (Fig. 3) agrees well with 2.8 x lo3 lug l-I, the ILC value for a 1.1 mm D. hydina (Horn, 1981; Table 5). The results of this comparison suggest that laboratory data may be directly applicable to the field where high food concentrations are involved, although data corresponding to more dilute concentrations should not be extrapolated without scrutiny.…”
Section: Comparison Of Ilc Valuessupporting
confidence: 71%
“…Nevertheless, a more detailed investigation of acclimation period should be carried out because the critical acclimation period may occur between 4 and 24 h, especially since Horn's (1981) 12 h acclimation produced an MFR which is substantially higher than those of Muck & Lampert's for the same copepod species. There was no obvious agreement between Eudiaptomus and Diaptomus with respect to acclimation effects since in the latter case, a longer acclimation period was associated with a greatly reduced filtering rate (Fig.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…Also the shorter and thicker spines may be effective against predators reducing for example Daphnia growth and reproduction (DeLange and Van Donk 1997). Defensive features that may give resistance to digestion include thick cell walls and mucilage (Horn 1981, Levitan 1987. Perhaps, the organisms may use several strategies to avoid predation, but if and how those characteristics will be affected by grazer-related chemical cues remains an open question.…”
Section: Phenotypic Plasticity In Desmodesmus and Scenedesmusmentioning
confidence: 99%
“…Lin et al (2014) also found that the minimum particle size ingested by Daphnia was 0.68 lm. The wide spectrum of particles ingested by Daphnia leads to a high individual filtration rate, which results in a high community filtration rate (Horn 1981). Several studies (Straile 2000(Straile , 2002Berger et al 2006;Schalau et al 2008) demonstrated that during spring and early summer Daphnia are a major controller of the phytoplankton dynamics in lakes and are responsible for what it is known as the clear water phase of a lake.…”
Section: Introductionmentioning
confidence: 99%